Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow\left(2x-7\right)^{2017}\left[\left(2x-7\right)^2-1\right]=0\)
=>(2x-7)(2x-6)(2x-8)=0
hay \(x\in\left\{3;\dfrac{7}{2};4\right\}\)
a, 2017-|x-2017| = x
=> |x - 2017| = 2017 - x
Th1: x \(\ge\)2017
=> x - 2017 = 2017 - x
=> x + x = 2017 + 2017
=> x = 2017 (thỏa mãn)
Th2: x < 2017
=> x - 2017 = -2017 + x
=> x - x = -2017 + 2017
=> 0 = 0
Vậy x = 2017
b, Vì \(\hept{\begin{cases}\left(2x-5\right)^{2018}\ge0\\\left(3y-7\right)^{2020}\ge0\\\left|x+y+z\right|\ge0\end{cases}\forall x,y,z}\)
\(\Rightarrow\left(2x-5\right)^{2018}+\left(3y-7\right)^{2020}+\left|x+y+z\right|\ge0\)
Mà \(\left(2x-5\right)^{2018}+\left(3y-7\right)^{2020}+\left|x+y+z\right|=0\)
Do đó \(\hept{\begin{cases}\left(2x-5\right)^{2018}=0\\\left(3y-7\right)^{2020}=0\\\left|x+y+z\right|=0\end{cases}\Leftrightarrow\hept{\begin{cases}2x-5=0\\3y-7=0\\x+y+z=0\end{cases}\Leftrightarrow}\hept{\begin{cases}x=\frac{5}{2}\\y=\frac{7}{3}\\z=\frac{-29}{6}\end{cases}}}\)
x = 4
=>(2x-7)^2017[(2x-7)^2-1]=0
=>(2x-7)(2x-8)(2x-6)=0
hay \(x\in\left\{3;3.5;4\right\}\)